MTL-Designer: An Integrated Flow for Analysis and Synthesis of Microstrip Transmission Line - Wang, Qipan; Liu, Ping; Jiang, Liguo; Liu, Mingjie; Lin, Yibo; Wang, Runsheng; Huang, Ru (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
Microstrip transmission line (MTL) appears extensively in microwave integrated circuits (MIC). To sufficiently analyze and synthesize the MTL, we propose MTL-Designer that can design the electrical and geometrical parameters of an MTL given performance specifications. We construct a deep generative model to generate initial solutions, and a surrogate model to predict the characteristics, optimize the solutions, and select from them. We further propose an adaptive sampling algorithm to speedup training. Our flow can generate 1000 feasible solutions within ∼0.6 s, realizing > 99.8% accuracy given various design specifications for two common MTL systems, exhibiting its strong potential for MIC design.